Oceanografia de estuários Amazônicos: Rio do Bombom (Viseu-PA) - SENA, Brenda Cristina Pinto de (2020)
This study aimed to characterize and evaluate the Bombom River estuary (Viseu city -PA) through physical, chemical, bathymetric and sedimentological parameters. The Bombom's estuary is located in the western portion of Viseu city, located in the northeastern Pará’s state. It has very humid climate with temperatures ranging around 27ºC, with two different seasonal periods (dry period occurring between July to December and rainy period from December to June) with a rainfall ranging in 2.500mm/year; presenting 5,7m semidiurnal macrotides. The sample were collected during the rainy period (February/2012), where two fixed strategic points were observed for measure the change of the tides, analysis of tides surface currents and physic-chemical properties, bathymetric survey and sediment samples along the estuary. The results obtained in the estuary of the Bombom River during observation period showed macrotides semidiurnal with values between 5,01 to -0,35m in tide curve of Bombom River. The surface current showed values of maximum 1,57m/s at low tide and minimum 0,04m/s in the low tide, being the average 0,63m/s. For the discharge values the profile 1 was 1.790.87m³.sˉ ¹ with ebb tide level and channel line of 4,32m in an 2.842,64m2 area. In profile 2 was 1.631,36m³.sˉ¹ with ebb tide level and channel line 3,81m in an 2.589,45m2 area. In profile 3 was 866,86m³.sˉ¹ with ebb tide level and channel line 6,72m in an 1.375,97m2 area. The bathymetry was divided into three sections, where the first section is represented by profile 1 presents the lower estuary sector of Bombom River with an 2,59m average depth, characterized with a single 4,32m deep channel line and 500m wide. The middle section is represented by profile 2 with an 2,68m average depth, this profile provides a single 3,81m deep channel line and 350m wide. The third section is represented by profile 1 represents the upper estuary with 3,25m average depth and a single 6,72m deep channel line and 150m wide. The superficial sediments showed in their textural composition sandy clays sediment type. The average particle size fraction presented predominant medium silt in granulometric fraction, the sorting was very poorly selected, the skewness was positive and the kurtosis varies between mesokurtic, platykurtic, very leptokurtic and very platykurtic. According to the Sherpard’s diagram the sediments were classified as sandy silt and according to the Pejurp diagram the environment has a high hydrodynamics. The physic-chemical parameters values observed were: temperature of 28,36°C; pH between 7,3 and 7,9; dissolved oxigen between 4,7 and 5,4mg/L, eletric condutivity between 50200 and 50900μs/cm; total dissolved solids between 25100 and 25400ppm and salinity between 32,8 and 33,2.